The Language of Paul Muldoon - Moi, Ruben (Costerus New Series, 2020)
This book interprets the multifarious writing of the Irish-American word wizard, Paul Muldoon, who has been described by The Times Literary Supplement as 'the most significant English-language poet born since the second World War'. Readership: All interested in poetry and writing from Ireland and the English-speaking world, and in the enigma of language.